Aniterative method for the solution of some singularly perturbed cauchy problems - Mel'nik, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We construct an iterative method for the solution of Cauchy problems for systems of singularly perturbed equations with fast time.